2008
DOI: 10.1104/pp.108.131227
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Rice HexokinasesOsHXK5andOsHXK6as Glucose Sensors    

Abstract: The Arabidopsis (Arabidopsis thaliana) hexokinase 1 (AtHXK1) is recognized as an important glucose (Glc) sensor. However, the function of hexokinases as Glc sensors has not been clearly demonstrated in other plant species, including rice (Oryza sativa).To investigate the functions of rice hexokinase isoforms, we characterized OsHXK5 and OsHXK6, which are evolutionarily related to AtHXK1. Transient expression analyses using GFP fusion constructs revealed that OsHXK5 and OsHXK6 are associated with mitochondria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
174
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(187 citation statements)
references
References 72 publications
9
174
2
2
Order By: Relevance
“…These results appear to be consistent with the role of Glc-6-P as a substrate for Suc synthesis via SPS, in contrast to the wild-type plants, where Suc was degraded. Our results show that increased HK activity in P SARK ::IPT plants is not associated with detrimental effects on photosynthesis and growth or in accelerating senescence, indicating that the differences between the regulation driven by changes in gene expression and protein activity might involve different signaling pathways, as suggested previously (Cho et al, 2009). …”
Section: Impact Of Ipt Expression On the Regulation Of C Metabolism Usupporting
confidence: 81%
See 2 more Smart Citations
“…These results appear to be consistent with the role of Glc-6-P as a substrate for Suc synthesis via SPS, in contrast to the wild-type plants, where Suc was degraded. Our results show that increased HK activity in P SARK ::IPT plants is not associated with detrimental effects on photosynthesis and growth or in accelerating senescence, indicating that the differences between the regulation driven by changes in gene expression and protein activity might involve different signaling pathways, as suggested previously (Cho et al, 2009). …”
Section: Impact Of Ipt Expression On the Regulation Of C Metabolism Usupporting
confidence: 81%
“…It has been shown that HK regulates photosynthesis, growth, and senescence. Increased levels of HK expression reduced growth and photosynthesis and induced senescence in tomato (Solanum lycopersicum) and rice plants (Dai et al, 1999;Cho et al, 2009) Supplemental Fig. S1): 1 (LOC_Os02g14110, aminotransferase), 1.2 (LOC_Os01g08270, aminotransferase), 1.3 (LOC_Os09g28050, aminotransferase), 1.4 (LOC_Os03g18810, aminotransferase), 1.5 (LOC_Os01g55540, aminotransferase), 2 (LOC_Os07g46460, Fd-GOGAT), 3 (LOC_Os02g20360, Tyr aminotransferase), 4 (LOC_Os04g52450, aminotransferase), 5 (LOC_Os08g01410, phosphate/phosphoenolpyruvate translocator), 6 (LOC_Os01g02020, acetyl-CoA acetyltransferase), 7 (LOC_Os07g42600, Ala aminotransferase), 8 (LOC_Os02g07160, glyoxalase family protein), 9 (LOC_Os04g14790, glycerol-3-phosphate dehydrogenase), 10 (LOC_Os02g41680, Phe ammonia-lyase), 11 (LOC_Os04g33300, amino acid kinase), 12 (LOC_Os02g37040, NTP3 [nitrate transporter]), 13 (LOC_Os04g45970, GDH), 14 (LOC_Os01g09000, glutaminyl-tRNA synthetase), 14.2 (LOC_Os07g07260, Gln-dependent NAD), 15 (LOC_Os02g38200, isocitrate dehydrogenase), 15.2 (LOC_Os01g46610, isocitrate dehydrogenase), 16 (LOC_Os02g10070, citrate synthase), 17 (LOC_Os03g05390, citrate transporter), 18 (LOC_Os04g31700, methylisocitrate lyase 2), 19 (LOC_Os10g08550, enolase), 20 (LOC_Os08g09200, aconitate hydratase), 20.2 (LOC_Os03g04410, aconitate hydratase), 21 (LOC_Os04g56400, Gln synthetase), 22.1 (LOC_Os06g16420, amino acid transporter), 22.2 (LOC_Os04g12499, amino acid transporter), 22.3 (LOC_Os06g36210, amino acid transporter), 22.4 (LOC_Os06g43700, amino acid transporter), 22.4 (LOC_Os11g09020, amino acid transporter), 22.5 (LOC_Os12g42850, amino acid permease), 22.6 (LOC_Os03g25869, amino acid permease), 22.7 (LOC_Os08g23440, amino acid permease), 22.8 (LOC_Os10g30090, amino acid permease), 22.9 (LOC_Os11g05690, amino acid permease), 22.10 (LOC_Os04g35540, amino acid transporter), 22.11 (LOC_Os08g03350, amino acid transporter), 22.12 (LOC_Os01g40410, amino acid transporter), 22.13 (LOC_Os01g63854, amino acid transporter), 22.14 (LOC_Os02g44980, amino acid transporter), 22.15 (LOC_Os02g09810, amino acid transporter), 22.16 (LOC_Os04g38680, amino acid transporter), 22.17 (LOC_Os05g50920, amino acid transporter), 22.18 (LOC_Os01g65000, ammonium transporter protein), 23.1 (LOC_Os02g34580, ammonium transporter protein), 23.2 (LOC_Os03g62200, ammonium transporter protein), 23.3 (LOC_Os04g43070, ammonium transporter protein), 24.1 (LOC_Os03g13240, peptide transporter PTR2), 24.2 (LOC_Os06g49250, peptide transporter PTR2), 24.3 (LOC_Os10g02240, peptide transporter PTR2), 24.4 (LOC_Os10g33170, peptide transporter PTR2), 24.5 (LOC_Os03g51050, peptide transporter PTR2), 25.1 (LOC_Os03g13274, NO 3 peptide transporter PTR2), 25.2 (LOC_Os10g42900, NO 3 peptide transporter PTR3), 26 (LOC_Os11g24450, 2-oxoglutarate/malate translocator), 27 (LOC_Os08g43170, hydroxymethylglutaryl-CoA synthase), and 28 (LOC_Os02g32490, acetyl-CoA synthetase).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, two hexokinases of rice (OsHXK5 and 6) also have been demonstrated to serve as glucose sensor and also their catalytically inactive forms still successfully delivered the sugar regulation, too [Cho et al (2009a), see Cho (2009b) for review]. However, the finding of the uncoupling of the metabolic and signaling activities of hexokinase unwittingly led to underscore the possible interaction of sugar signaling with the cellular metabolic status.…”
Section: Discussionmentioning
confidence: 99%
“…The amplified product was digested with XbaI and XhoI and was cloned into the region between the CaMV35S promoter and sGFP of the JJ461 binary vector (Cho et al, 2009). The primers used were 5#-GCTCTAGACTCTTCTGAACTAACCCAAA-GAT-3# and 5#-CCCTCGAGATCGGTGACCTCTCCTCCTTGAT-3# (the underlined sequences indicate XbaI and XhoI sites, respectively).…”
Section: Construction Of the Ossut2-gfp Fusion Vector And Subcellularmentioning
confidence: 99%